Analysis of Financial Performance In PT. PP (Persero) Tbk - Muhammad Fadil Abu Bakar; Youlanda Hasan (Tasharruf: Journal Economics and Business of Islam, 2019)
AbstractTo find out financial performance PT. PP (Persero) Tbk.               Data analysis in this study uses quantitative descriptive by comparing the company's financial ratios using the Liquidity Ratio, Solvability Ratio, Activity Ratio, Solvability Ratio               Based on the results of the analysis it can be concluded that the financial performance of PT. PP (Persero) Tbk. in 2014 until 2016 where the liquidity ratio felt in a liquid state because it was in the financial ratio. The solvency ratio is in an unhealthy state, because the debt to equity ratio and debt to asset ratio are below the standard financial ratio. The activity ratio is in good condition, because the receivable turn over and inventory turn over are at the financial ratio standard. The profitability ratio is in an unhealthy state, because the net profit margin and return of investment are below the standard financial ratio.Keywords: Liquidity Ratio, Solvability Ratio, Activity Ratio, Profitability Ratio.